The effect of leachable components of resin cements and its resultant bond strength with lithium disilicate ceramics - M V Mavishna; Kondas Vijay Venkatesh; Dhanasekaran Sihivahanan (Wolters Kluwer Medknow Publications, 2020)
Objectives: To evaluate the leachable components of resin cements in oral simulating fluids using high performance liquid chromatography and its resultant shear bond strength with ceramics. Methods: Forty extracted permanent human mandibular molar teeth were sectioned horizontally with a disc beneath the dentino-enamel junction to expose the coronal dentin surface and later finished with 600-grit silicon carbide paper to create a uniform flat surface. Forty Lithium Di-silicate Ceramic block cylinders were sliced in a saw cutting machine at 250 rpm under water-cooling to obtain the discs. The teeth and the ceramic discs were then randomly assigned to two groups on the basis of material used for luting the ceramic disk. Group I: Ceramic disc luted with tooth surface using Variolink II Dual cure Resin Cement, Group II: Ceramic disc luted with tooth surface using multilink speed self-adhesive self-curing resin cement. All ceramic discs were etched with 5% HF acid (IPS Ceramic Etching Gel, Ivoclar, Schaan, Liechtenstein) for 20 seconds, then rinsed thoroughly for 20 seconds and dried for 20 seconds. Ceramic specimens were luted on dentin surfaces with the application of 5 kg load. The samples were stored in 75% ethanol solution for 2 weeks at 37 degree Celsius for chemical aging. HPLC Analysis were performed to analyze the eluted monomer. After HPLC Analysis, Samples were then loaded using universal testing machine for the evaluation of shear bond strength between ceramic discs and the resin cements before and after the elution of monomers. Results: Under HPLC analysis, results showed that the peak release of monomer is Bis-GMA in both the groups. The shear force required to break the bond between the ceramic luted to tooth surface with the resin cements were more for Group I. Statistical results: The statistical analysis was done using ANOVA and paired t-test and it shows P value ≥0.05, hence the null hypothesis is rejected. Conclusion: The monomer eluded from all the groups are identified as Bis-GMA, The eluded monomer decreases the bond strength between the resin cement and the ceramic due to water sorption, The Variolink II (dual cure) resin cement shows improved bond strength than the Multilink (self-cure self-adhesive) resin cement.